Analisis Pengaruh Media Pembelajaran dan Kemampuan Berpikir Kreatif Terhadap Hasil Belajar PAI SMP Islam Al-Ashriyah - Zinnurain Zinnurain (UNDIKMA, 2022)
This study aims to determine the effect of learning media and creative thinking skills on learning outcomes of Islamic Religious Education (PAI) at Al-Ashriyah Sesela Islamic Middle School. The research method used in this study is an experimental with a treatment design by level 2x2. The instrument used was a questionnaire. The research subjects were students of class VII A and B of Islamic Middle School Al-Ashriyah Sesela, totaling 36 students. Divided into two classes with different learning media, 18 people with interactive learning media and 18 people with conventional media. Samples were taken using a multi-stage random sampling technique. The results of the research are: (1) From learning the Educational Communication System, students who use interactive learning media are higher than those who use conventional learning media; (2) There is an interaction between learning media and creative thinking skills on the learning outcomes of Islamic Religious Education (PAI); (3) Students with high creative thinking skills, the group of students who learn to use interactive learning media is higher than the group of students who learn to use conventional learning media. (4) For students with low creative thinking skills, the group of students who learn to use interactive learning media is lower than the group of students who learn to use conventional learning media.